2006
DOI: 10.1007/s10029-006-0122-2
|View full text |Cite
|
Sign up to set email alerts
|

A case of a large retroperitoneal liposarcoma presenting as an incarcerated inguinal hernia

Abstract: We report a rare case of retroperitoneal liposarcoma developing within an incarcerated inguinal hernia. A 53-year-old man presented to our hospital with left inguinal mass. Preoperative computed tomography revealed an intraabdominal huge mass, and a clinical diagnosis of liposarcoma. Physical findings except for the inguinal mass and laboratory examination, including tumor markers (CEA, CA19-9), were within normal range. Intraoperatively, the mass was incarcerated in the inguinal canal and involved the left te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…On histological examination, most specimen was diagnosed as well-differentiated liposarcomas, comprised of 7 cases. 5,7,8,1012 The large tumors' weight ranged widely from 1.26 kg in the presented case up to 42 kg. 9 R0 resection margins are documented in only 2 cases after primary surgery.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…On histological examination, most specimen was diagnosed as well-differentiated liposarcomas, comprised of 7 cases. 5,7,8,1012 The large tumors' weight ranged widely from 1.26 kg in the presented case up to 42 kg. 9 R0 resection margins are documented in only 2 cases after primary surgery.…”
Section: Resultsmentioning
confidence: 71%
“…Side of the body was almost evenly distributed with 5 right-sided 68,10 and 4 left-sided 913 manifestations. Three cases appeared as an incarcerated hernia, 11,14 of note one tumor appeared as a reducible hernia 8 ; the others were not documented. In 5 cases a computed tomography scan was performed preoperatively 6,911,13 ; notably none of them was conducted due to the combined suspicion of an inguinal hernia and a retroperitoneal tumor.…”
Section: Resultsmentioning
confidence: 97%
“…La exploración física demuestra una masa sólida irregular con transiluminación negativa. El diagnóstico preoperatorio no es común, lo habitual es un hallazgo incidental intraoperatorio en el contexto de una cirugía realizada al suponer alguna de las patologías que se incluyen en el diagnóstico diferencial; en este caso clínico el diagnóstico fue en el curso de una cirugía urgente realizada por sospecha de hernia inguinal incarcerada [23][24][25] . Pero en caso de sospecha preoperatoria las pruebas complementarias indicadas serían la TC o la RM.…”
Section: Discussionunclassified
“…Previously, only a few published case reports of inguinal hernia were available, and they discussed an LPS protruding from the retroperitoneum. [4][5][6][7][8][9]12,13 Although 6 is a small number for reliable statistical analysis, we showed that RLPS protruding into the inguinal canal has poor prognosis compared with inguinoscrotal LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few case reports describe RLPS presenting as an inguinal hernia. [4][5][6][7][8][9] Sometimes, a protruding mass in the inguinal region is the only symptom, resulting in a misdiagnosis of ordinary inguinal hernia.…”
mentioning
confidence: 99%